TRANSLATING LITERARY WORKS IS A BIG RESPONSIBILITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 14 November 2016 – Translating major literary works from Malay to English and vice versa is a big responsibility upon those who have the capability of doing so.